European Reference Networks: Share, Care, and Cure—Future or Dream? - Wijnen, Rene; Anzelewicz, Stefan Michał; Petersen, Claus; Czauderna, Piotr (European Journal of Pediatric Surgery, 2017)
European Reference Networks (ERNs) are virtual networks that involve healthcare providers across Europe. The aim of ERNs is to tackle complex or rare diseases and conditions that necessitate highly specialized treatment, knowledge and resources.This article summarizes the concept of European Reference Networks in the European Union, legislation and policy behind ERNs from the standpoint of pediatric surgical specialty. There are seven ERNs in which pediatric surgeons are involved, four of which are being discussed, namely ERN PaedCan, eUROGEN ERN, ERN RARE-LIVER and ERNICA. ERNs program is a step towards improving health care quality, reducing access inequalities, and increasing overall medical experience and knowledge but its final impact is yet to be determined.
Keywords: rare diseases; children; networking